Strengthening Community Health and Economy through Local Herbal Innovation in the Harmoni Women’s Group - Yulita Maulani; Aptika Oktaviana Trisna Dewi; Sri Wulandari; Erika Novi Ardianti; Anisa Indriyani; Dini Ashfi (Universitas Muhammadiyah Surakarta, 2025)
A community service program based on the utilization of family medicinal plants (TOGA) serves as a strategic approach to improving health literacy and economic independence among women in urban areas. Background: Although TOGA is an essential part of Indonesia’s cultural heritage, its community-level application remains limited due to restricted land availability, low cultivation skills, inadequate hygienic processing practices, and limited entrepreneurial capacity. Purpose: This program aims to empower women by optimizing the use of TOGA and developing innovative local herbal products to enhance health literacy and strengthen economic independence. Methods: The program was conducted over eight months in 2025 and involved 15 participants aged 25–60 years. The implementation included training on TOGA cultivation using vertical and hydroponic techniques, training on processing rhizomes into instant herbal beverages with simple technology and food sanitation principles, and entrepreneurship training covering branding, digital marketing, and environmentally friendly packaging design. Evaluation methods consisted of pre-tests, post-tests, direct observation, and participant feedback. Results: Significant improvements were observed across multiple indicators, including increases in TOGA knowledge (52–85), awareness of benefits (58–90), cultivation skills (60–80), and daily utilization (58–85). Knowledge related to herbal products also improved, including perceptions of benefits (60–95), product variety (55–85), production processes (70–88), and business opportunities (62–90), while entrepreneurial understanding increased by 27–35 points. Conclusion: The program effectively enhanced participants’ health literacy, technical skills, product innovation, and entrepreneurial readiness while contributing to the achievement of SDG 3, SDG 8, and SDG 12. Recommendations: Program sustainability may be strengthened through the establishment of collaborative business groups and the expansion of digital marketing networks to increase the economic impact of local herbal-based empowerment initiatives.